2001
DOI: 10.1039/b101434j
|View full text |Cite
|
Sign up to set email alerts
|

The reactions of atomic chlorine with acrolein, methacrolein and methyl vinyl ketone

Abstract: An investigation into the reactions between Cl atoms and acrolein (1), methacrolein (2) and methyl vinyl ketone (3)is presented. Values of the rate constants for the reactions have been determined by an absolute technique for the Ðrst time. At a pressure of 1.6 Torr, the rate constants obtained were :6 in units of 10~10 cm3 molecule~1 s~1. was also determined at atmospheric pressure using k 3 \ 0.99 ^0.20 k 1 a relative-rate technique. The rate constant obtained was (2.2 ^0.3) ] 10~10 cm3 molecule~1 s~1 ; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 20 publications
9
39
1
Order By: Relevance
“…The CO observed by Fantechi et al [29], but not seen in our work, may result from oxidation of the primary CH 2 O product. Canosa-Mas et al [40] report the observation of chloroacetaldehyde and CH 2 O (in agreement with our work, though no yield data were given), and CO (yield ≈0.05). They also conclude that external addition of Cl to the MVK double bond leads to Fig.…”
Section: Mvksupporting
confidence: 95%
See 2 more Smart Citations
“…The CO observed by Fantechi et al [29], but not seen in our work, may result from oxidation of the primary CH 2 O product. Canosa-Mas et al [40] report the observation of chloroacetaldehyde and CH 2 O (in agreement with our work, though no yield data were given), and CO (yield ≈0.05). They also conclude that external addition of Cl to the MVK double bond leads to Fig.…”
Section: Mvksupporting
confidence: 95%
“…The only previous studies of the Cl-initiated oxidation of MVK were brief investigations by Fantechi et al [29] and Canosa-Mas et al [40]. Products identified in [29] were chloroacetaldehyde, HCOCl, methylglyoxal, CH 2 O, HCl, CO, and CO 2 ; no yields are reported.…”
Section: Mvkmentioning
confidence: 94%
See 1 more Smart Citation
“…If the reaction occurs only through addition to the vinyl group, substitution of a hydrogen atom by chlorine on the terminal methyl group does not alter the rate constant, consistent with our observation and that of Canosa-Mas et al 34 that abstraction represents less than 3% of the overall reaction.…”
Section: Impact Of Chlorine Substitution On Rate Constantsupporting
confidence: 81%
“…Kinetics studies of the reactions of chlorine atoms with ACR, MACR, CA and MVK have been reported recently, [32][33][34][35] but there are no reports of the rate constants for the CCA or CMVK reactions. Our combined data set permits probing structure-reactivity relationships for this series of unsaturated aldehydes and ketones.…”
Section: à3mentioning
confidence: 99%